Applications of management science in banking and finance - Fowkes, Terence R. (London : Gower Press, 1972)
The book is on Operational Research and Management Science as it relates to Banking and Finance.
Includes bibliographical footnotes and index.
usc 17/05/2017
Loans
Keywords: Bank management; Finance; Corporations